A Thermochromic, Viscoelastic Nacre-like Nanocomposite for the Smart Thermal Management of Planar Electronics - Wang, Jiemin; Yang, Tairan; Wang, Zequn; Sun, Xuhui; An, Meng; Liu, Dan; Zhao, Changsheng; Zhang, Gang; Lei, Weiwei (Nano-Micro Letters, 2023)
Cutting-edge heat spreaders for soft and planar electronics require not only high thermal conductivity and a certain degree of flexibility but also remarkable self-adhesion without thermal interface materials, elasticity, arbitrary elongation along with soft devices, and smart properties involving thermal self-healing, thermochromism and so on. Nacre-like composites with excellent in-plane heat dissipation are ideal as heat spreaders for thin and planar electronics. However, the intrinsically poor viscoelasticity, i.e., adhesion and elasticity, prevents them from simultaneous self-adhesion and arbitrary elongation along with current flexible devices as well as incurring high interfacial thermal impedance. In this paper, we propose a soft thermochromic composite (STC) membrane with a layered structure, considerable stretchability, high in-plane thermal conductivity ( 30 W m−1 K−1), low thermal contact resistance ( 12 mm2 K W−1, 4–5 times lower than that of silver paste), strong yet sustainable adhesion forces ( 4607 J m−2, 2220 J m−2 greater than that of epoxy paste) and self-healing efficiency. As a self-adhesive heat spreader, it implements efficient cooling of various soft electronics with a temperature drop of 20 °C than the polyimide case. In addition to its self-healing function, the chameleon-like behavior of STC facilitates temperature monitoring by the naked eye, hence enabling smart thermal management. Highlights: 1 Construction of a viscoelastic composite nacre with a ripple-like layered architecture through supramolecular interactions. 2 Outstanding self-adhesion, self-healing and scrape-resistant mechanical and thermal properties. 3 Utility as an integrated heat spreader and TIMs for “chameleon-like” thermal management of planar soft electronics.